Optimal Switching Instants for the Control of Hybrid Systems - Mullier, Olivier; Alexandre dit Sandretto, Julien; Chapoutot, Alexandre (Acta Cybernetica, 2020)
The problem of determining optimal switching instants for the control of hybrid systems under reachability constraints is considered. This optimization problem is cast into an interval global optimization problem with differential constraints, where validated simulation techniques and dynamic time meshing are used for its solution. The approach is applied on two examples, one being the well-known example of the Goddard's problem where a rocket has to reach a given altitude while consuming the smallest amount of fuel.